THE ROLE OF ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING IN PRECISION TARGETING: REVOLUTIONIZING MARKETING STRATEGIES - Silvia Ekasari; Loso Judijanto; Arnes Yuli Vandika (CV. Adiba Aisha Amira, 2024)
Digital marketing has undergone rapid evolution in recent years. The development of machine learning and artificial intelligence (AI) is one of the major shifts affecting the marketing environment (ML). This technology has completely changed how businesses engage with their clientele and maximize their advertising budgets. Artificial intelligence refers to the ability of a computer or system to imitate human intelligence. In the context of digital marketing, AI can be used to quickly and efficiently analyze data, identify patterns and provide valuable insights. With artificial intelligence, companies can make smarter decisions and optimize their marketing campaigns based on deeply analyzed data. The method used in this article is the study method. Literature studies can be obtained from various sources, including journals, books, documentation, the internet and libraries. This research discusses the definition of AI and ML, the transformation of the marketing sector by digital platforms and data analytics, the exploration of precision marketing and its increasing relevance in the digital era, the role of AI and ML in data mining for precision targeting, the contribution of AI in creating more granular customer segments, and the study of ML in predictive analytics to anticipate customer behavior.